The Tension Between Women's Rights and Religious Rights: Reservations to CEDAW by Egypt, Bangladesh and Tunisia - Brandt, Michele (Journal of law and religion, 1995)
Since women's rights first entered the agenda of the United Nations ("U.N."), there has been a running tension between the expression and codification of those rights and the right to freedom of religion. Thus far, this tension has resulted in an uneasy relationship between U.N. instruments regarding religious rights and U.N. instruments on women's rights. The former stand mute with respect to the relationship between women's rights and religion. The latter are encumbered with substantial reservations by countries concerned with safeguarding their religious tenets and traditions.This paper will examine the tension between women's rights and religious rights as expressed in certain State Parties' reservations to the Convention on the Elimination of All Forms of Discrimination Against Women ("CEDAW") that are based on Islamic Law and the extent to which CEDAW can ensure adherence to its norms while recognizing the right to freedom of religion or belief. The article does not purport to offer any authoritative commentary of Islamic law. Rather, its objective is to highlight connections between CEDAW's tenets, the nature of Islam-based reservations, and the course of women's lives in certain reserving countries.